Chaucer's legendary good women - Percival, Florence (Cambridge studies in medieval literature ;, 1998)
Chaucer's Legend of Good Women is a testament to the disparate views of women prevalent in the Middle Ages. Dr Percival contends that the complex medieval notion of Woman informs the structure of the poem: in the Prologue Chaucer praises conventional ideas of female virtue, while in the Legends he demonstrates a humorous scepticism, apparently influenced by a contemporary antifeminist tradition. The debate Chaucer thus promotes could be relied on to entertain many medieval readers, at the same time that it demonstrates the power of the vernacular translator/poet to handle language wittily and to do just as he pleases with the august texts of the past. This is a comprehensive account of the Legend's interpretative puzzles, which does not ignore the element of political writing, and adds to a close and nuanced reading of the text an examination of literary, historical, and social contexts.